Formulation of Bio-Based Washing Agent and Its Application for Removal of Petroleum Hydrocarbons From Drill Cuttings Before Bioremediation - Arpornpong, Noulkamol; Padungpol, Rattiya; Khondee, Nichakorn; Tongcumpou, Chantra; Soonglerdsongpha, Suwat; Suttiponparnit, Komkrit; Luepromchai, Ekawan (Frontiers in Bioengineering and Biotechnology, 2020)
Drill cuttings from petroleum exploration and production sites can cause diverse environmental problems. Total petroleum hydrocarbons (TPHs) are a major pollutant from the use of polyolefin-based mud. As an alternative to incineration, this study investigated the application of surfactant-enhanced washing technology prior to bioremediation. The washing step was necessary because the initial TPH concentrations were quite high at approximately 15% (w/w). Washing agents were formulated by varying the concentration of lipopeptide biosurfactant (in foamate or cell-free broth), Dehydol LS7TH (fatty alcohol ethoxylate 7EO, oleochemical surfactant) and butanol (as a lipophilic linker) at different salinities. The most efficient formula produced a Winsor Type I microemulsion (oil-in-water microemulsion) with polyolefin and contained only 20% (v/v) foamate and 2% (v/v) Dehydol LS7TH in water. Due to the synergistic behavior between the anionic lipopeptides and non-ionic Dehydol LS7TH, the formula efficiently removed 92% of the TPHs from the drill cuttings when applied in a jar test. To reduce the cost, the concentrations of each surfactant should be reduced; thus, the formula was optimized by the simplex lattice mixture design. In addition, cell-free broth, at a pH of 10, containing 3.0 g/L lipopeptides was applied instead of foamate because it was easy to prepare. The optimized formula removed 81.2% of the TPHs and contained 72.0% cell-free broth and 1.4% Dehydol LS7TH in water. A 20-kg soil washing system was later tested where the petroleum removal efficiency decreased to 70.7% due to polyolefin redeposition during separation of the washing solution. The remaining TPHs (4.5%) in the washed drilled cuttings were further degraded by a mixture of Marinobacter salsuginis RK5, Microbacterium saccharophilum RK15 and Gordonia amicalis JC11. To promote TPH biodegradation, biochar and fertilizer were applied along with bacterial consortia in a microcosm experiment. After 49-day incubation, the TPHs were reduced to 0.9% by both physical and biological mechanisms, while the TPHs in the unamended samples remained unaffected. With the use of the formulated bio-based washing agent and bioremediation approach, the on-site treatment of drill cuttings could be conducted with an acceptable cost and low environmental impacts.